Video Nicos Weg dalam Peningkatan Kosakata Bahasa Jerman - Muslima, Nur; Achmad, Abdul Kasim; Anwar, Muhammad (Academic : Journal of Social and Educational Studies, 2024)
Abstract. This study aims to improve the German vocabulary of students of class XI IPS 4 SMA Negeri 14 Makassar through Nicos Weg video. This research is a classroom action research consisting of two cycles with each cycle consisting of planning, implementation, observation and reflection stages. This research data consists of two types of data, namely qualitative data which is a description of the results of implementation and observation during the learning process and quantitative data in the form of students vocabulary improvement test results. The average vocabulary score obtained by the students in Cycle I was 53.16 and in Cycle II the average value obtained by the students was 67.5. The results showed that the Nicos Weg video can improve the German vocabulary of students in Class XI IPS 4 SMA Negeri 14 MakassarKeywords: Vocabulary Improvement, Nicos Weg Video, Classroom Action Research